1997
DOI: 10.1111/j.1651-2227.1997.tb15178.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microflora of Estonian and Swedish infants

Abstract: The intestinal microflora of 1-y-old healthy Estonian (n = 27) and Swedish infants (n = 29) was studied by quantitative culture of faecal samples. The major differences were high counts of lactobacilli and eubacteria in the former and increased numbers of clostridia in the latter babies. Bifidobacteria and anaerobic cocci prevailed equally in both groups, while eubacteria and enterococci were the major microorganisms in many Estonian infants and bacteroides and clostridia in many Swedish infants. The microflor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
232
2
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(249 citation statements)
references
References 27 publications
9
232
2
6
Order By: Relevance
“…Large geographical variations in the composition of gastrointestinal microflora in infants have been observed (100,101). A comparison between Sweden and Estonia revealed a more intensive colonization with lactobacilli among the Estonian infants, whereas the Swedish infants Bodner, 1998 Cross-sectional Common childhood infections 84 Farooqi, 1998 Cross-sectional Common childhood infections 85 Strannegård, 1998 Cross-sectional Mycobacteria 86 Bolte, 2003 Longitudinal (prosp) LPS in home (mattress) dust 97 Wickens, 2002 Cross-sectional Unspecified (farming) 122 Palmer, 2002 Cross-sectional Ascaris lumbricoides 137 Dold, 1998 Cross-sectional Ascaris sp.…”
Section: Exposure To Commensals In the Gastrointestinal Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…Large geographical variations in the composition of gastrointestinal microflora in infants have been observed (100,101). A comparison between Sweden and Estonia revealed a more intensive colonization with lactobacilli among the Estonian infants, whereas the Swedish infants Bodner, 1998 Cross-sectional Common childhood infections 84 Farooqi, 1998 Cross-sectional Common childhood infections 85 Strannegård, 1998 Cross-sectional Mycobacteria 86 Bolte, 2003 Longitudinal (prosp) LPS in home (mattress) dust 97 Wickens, 2002 Cross-sectional Unspecified (farming) 122 Palmer, 2002 Cross-sectional Ascaris lumbricoides 137 Dold, 1998 Cross-sectional Ascaris sp.…”
Section: Exposure To Commensals In the Gastrointestinal Tractmentioning
confidence: 99%
“…showed increased numbers of clostridia, especially C. difficile (101). Bjo¨rksten et al (102) examined further whether atopic diseases among children are associated with differences in their intestinal microflora in Estonia with a low and in Sweden with a high prevalence of atopy at the age of 2 years.…”
Section: Exposure To Commensals In the Gastrointestinal Tractmentioning
confidence: 99%
“…The results of a comparative study of Estonian and Swedish children demonstrated that there are indeed differences in the intestinal micro¯ora. In Estonia, the typical micro¯ora includes more lactobacilli and fewer clostridia, a condition which is associated with a lower presence of atopic disease (73).…”
Section: The Lifestyle Factors Which Have Been Proposed So Farmentioning
confidence: 99%
“…Children in Estonia have lower rates of atopy than Swedish children and their intestinal microflora contains a larger amount of lactobacilli. 10 Lactobacillus plantarum, most common in spontaneously fermented vegetables, can colonise the human intestinal mucosa and affect indigenous strains. 11 Animal experiments and studies in vitro have shown that lactobacilli can change the interleukin profile and inhibit antigen-induced IgE production.…”
Section: Introductionmentioning
confidence: 99%